Impact of betablockers on general and local outcome in patients hospitalized for lower extremity peripheral artery disease: The COPART Registry. Issue 5 (February 2017) - Mirault, Tristan; Galloula, Alexandre; Cambou, Jean-Pierre; Lacroix, Philippe; Aboyans, Victor; Boulon, Carine; Constans, Joel; Bura-Riviere, Alessandra; Messas, Emmanuel
Abstract : Abstract: Lower extremity peripheral artery disease (PAD) is one manifestation of atherosclerosis. Patients with PAD have an increased rate of mortality due to concurrent coronary artery disease and hypertension. Betablockers (BB) may, therefore, be prescribed, especially in case of heart failure. However, BB safety in PAD is controversial, because of presumed peripheral hemodynamic consequences of BB that could lead to worsening of symptoms in patients with PAD. In this context, we aimed to determine the impact of BB on all-cause and cardiovascular mortality and amputation rate at 1 year after hospitalization for PAD from the COPART Registry population. This is a prospective multicenter observational study collecting data from consecutive patients hospitalized for PAD in vascular medicine departments of 4 academic hospitals in France. Patients with, either claudication, critical limb ischemia or acute lower limb ischemia related to a documented PAD were included. We compared the outcomes of patients with BB versus those without BB in their prescription list at hospital discharge. The mean age of the study population was 70.9 years, predominantly composed of males (71%). Among the 1267 patients at admission, 28% were treated by BB for hypertension, prior myocardial infarction or heart failure. During their hospital stay, 40% underwent revascularization (including bypass surgery 29% and angioplasty 74%), 17% required an amputation, and 5% died. In a multivariate analysis, only prior myocardial infarction was found associated with BB prescription with an odds ratio (OR) of 3.11, P < 0.001. Conversely, chronic obstructive pulmonary disease or PAD with ulcer impeded BB prescription (OR: 0.57 and 0.64, P = 0.007; P = 0.001, respectively). One-year overall mortality of patients with BB did not differ from those without (23% vs. 23%, P = 0.95). The 1-year amputation rate did not differ either (4% vs. 6%, P = 0.14). Patients hospitalized for PAD with a BB in their prescription did not worsen their outcome at 1 year compared to patients without BB. Based on these safety data, prospective study could be conducted to assess the effect of BB on long-term mortality and amputation rate in patients with mild, moderate, and severe PAD.